Impact of Online Teaching Experience During Covid-19 Pandemic on Psychological Health: Moderating Role of Coping Strategy - Ammar Ahmad; Mazhar Iqbal; M. Zubair, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This study aims to examine the problems faced by high school teachers during COVID19 pandemic and its impact on psychological health: moderating role of coping strategies. Cross sectional research method was used; a sample of 200 was selected from high school teachers from Islamabad and Kohat through purposive sampling. An online teaching questionnaire was used for measuring the online teaching experience of high school teachers. The DASS scale was used to measure the psychological health of high school teachers, and for coping strategies, select Brief-Coping Scale. Furthermore, the findings of this study demonstrates that significant positive association of online teaching experience questionnaire and its sub scale with BriefCope Scale (Problem focused coping), Brief-Cope Scale (Emotion focused coping), BriefCope Scale (Avoidant coping), and Brief-Cope Scale Total. The result also shows no association of online teaching experience scale with psychological health sub scales depression, anxiety, and stress. the findings further show the moderation between online teaching experience, coping strategies, and psychological health the results show the moderation between all the three variables.